Randomized Trial of Print Messaging: The Role of the Partner and Monitoring Style in Promoting Provider Discussions about Prostate Cancer Screening Among AA Men - Miller, Suzanne M. (2013)
OBJECTIVE: Although AA men are at elevated risk for prostate cancer (Pca), medical guidelines do not present consistent screening recommendations for this group. However, all guidelines stress the need for screening decision making with a provider. This study evaluated the effectiveness of a brochure designed for the female partners of AA men, designed to help promote such discussion on the part of their mates. We also explored the effect of the partner's monitoring style (i.e., the extent to which the partner typically attends to health threats) on promoting discussion. METHODS: Female partners of AA men (N=231) were randomized to receive either a Pca screening CDC brochure for AA men, combined with a “partner” brochure containing strategies to promote men's initiation of a provider visit to discuss screening, or the CDC brochure only, and completed pre- and post-intervention surveys online. RESULTS: The message groups did not differ on taking active steps to engage in provider discussion: relative risk ratio (RRR) = 0.99, p = .98; thinking about it: RRR= 1.13, p = .74. However, among partners who received the partner brochure, monitoring style was associated with “thinking about initiating a provider visit” on the part of the mate (RRR = 1.74, p<.01). Across conditions, monitoring style was also associated with “taking active steps to initiate a provider visit” on the part of the mate (RRR = 1.38, p < .05). CONCLUSIONS: High monitoring partners may be effective in influencing their AA mates to initiate provider discussion, particularly when tailored messaging is provided.